A comparison of the effects of haptic and visual feedback on presence in virtual reality. Issue 157 (January 2022) - Gibbs, Janet K.; Gillies, Marco; Pan, Xueni
Highlights: Comparing contribution of Haptic, Visual and bimodal feedback to Presence in VR. Bimodal feedback enhances presence compared with Haptic or Visual alone. Visual alone does not give a better sense of presence than Haptic alone. Varying the location of events enhances presence regardless of feedback modality. Abstract: In the current consumer market, Virtual reality experiences are predominantly generated through visual and auditory feedback. Haptics are not yet well established, but are increasingly introduced to enhance the user's sense of 'reality'. With haptic (vibrotactile) feedback now part of the built-in mechanism of VR consumer devices, there is an urgent need to understand how different modalities work together to improve the user experience. This paper reports an experiment that explores the contributions made to participants' sense of presence by haptic and visual feedback in a virtual environment. Participants experienced a virtual ball bouncing on a virtual stick resting across their avatar hands. We found that presence was enhanced when they could both see and feel the ball's action; with a strong suggestion that haptic feedback alone gave rise to a greater sense of presence than visual alone. Similarly, whilst visual or bimodal feedback enhanced participants' ability to locate where the ball bounced on the stick, our results suggest that the action itself was more readily discerned haptically than visually.